Lost legacy ebook - Mentink, Dana (Treasure Seekers., 2023)
Brooke Ramsey is running out of time. She needs to save her father's reputation before she loses him to illness. That means finding the painting that went missing while in his care. Fast. Which is why she teams up with Victor Gage, owner of Treasure Seekers agency. The charming private detective has more at stake than uncovering a lost masterpiece. He's investigating his wife's death, and the artwork holds the answer. As Victor and Brooke draw closer to each other, so does a murderer. Someone wants the past to remain buried and will kill again to keep it hidden.